Analysing trust as a means of improving the effectiveness of the virtual supply chain. (20th June 2008) - Paterson, Ian; Maguire, Heather; Al-Hakim, Latif
This article focuses on trust within interorganisational virtual organisations, which are regarded as legally separate but operationally interdependent companies focused on responding to a market opportunity and facilitated by ICT as a medium for communication and coordination. The context of the research described in this paper is the Australian meat and horticulture supply chains. Within the context of these two supply chains the perceived importance and perceived levels of 12 trust factors are investigated. The research identifies three trust factors demonstrating critical gaps between the expected performance level and the perceptions of actual performance common to the meat and horticulture supply chains. These factors were information sharing, reliability and work standard. Two other critical factors were identified in the meat supply chain, i.e., timeliness and customisation, while three other critical factors were identified as specifically relating to the horticulture supply chain, i.e., shared values, POS information and honesty and integrity.